THE ISSUE OF EQUIVALENCE IN TRANSLATION - Quvvatova Mehribon Usan qizi (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
This article discusses the issue of equivalence in translation, its theoretical background, and the various approaches developed by translation scholars. The paper examines the emergence and development of the concept, its significance in the translation process, and the linguistic, semantic, and pragmatic aspects influencing equivalence. It also explores the relationship between linguistic form, communicative purpose, and cultural adaptation, emphasizing the translator’s competence and creativity as decisive factors in achieving equivalence between the source and target texts.